Effects of PI and PIII snake venom haemorrhagic metalloproteinases on the microvasculature: a confocal microscopy study on the mouse cremaster muscle - Herrera Arias, Cristina (2016)
The precise mechanisms by which Snake Venom Metalloproteinases (SVMPs) disrupt the microvasculature and cause haemorrhage have not been completely elucidated, and novel in vivo models are needed. In the present study, we compared the effects induced by BaP1, a PI SVMP isolated from Bothrops asper venom, and CsH1, a PIII SVMP from Crotalus simus venom, on cremaster muscle microvasculature by topical application of the toxins on isolated tissue (i.e., ex vivo model), and by intra-scrotal administration of the toxins (i.e., in vivo model). The whole tissue was fixed and immunostained to visualize the three components of blood vessels by confocal microscopy. In the ex vivo model, BaP1 was able to degrade type IV collagen and laminin from the BM of microvessels. Moreover, both SVMPs degraded type IV collagen from the BM in capillaries to a higher extent than in PCV and arterioles. CsH1 had a stronger effect on type IV collagen than BaP1. In the in vivo model, the effect of BaP1 on type IV collagen was widespread to the BM of arterioles and PCV. On the other hand, BaP1 was able to disrupt the endothelial barrier in PCV and to increase vascular permeability. Moreover, this toxin increased the size of gaps between pericytes in PCV and created new gaps between smooth muscle cells in arterioles in ex vivo conditions. These effects were not observed in the case of CsH1. In conclusion, our findings demonstrate that both SVMPs degrade type IV collagen from the BM in capillaries in vivo. Moreover, while the action of CsH1 is more directed to the BM of microvessels, the effects of BaP1 are widespread to other microvascular components. This study provides new insights in the mechanism of haemorrhage and other pathological effects induced by these toxins.